HUBUNGAN KADAR ENZYM KHOLINESTERASE DENGAN KADAR HORMON THYROID PADA WUS DI DAERAH GONDOK ENDEMIK - Sukati S.; Suryati K.; M. Ichsan; Mucherdiyantiningsih Mucherdiyantiningsih; Djoko Kartono (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2006)
The Relationship Between Cholinesterase Enzym and Iodine Status of Child Bearing Age Woman (CBAW) In The Endemic Goitre Area.Background: Pesticide as a pollutant substance is a goitrogenic agent. It can form a strong complex bound with iodine in the body. Women who ive in the endemic goiter, area where the iodine source in the nature is limited and frequently exposed by pesticide, can increase the prevalence of iodine deficiency disorder (IDD).Objectives: To find out the relationship between cholinesterase enzyme concentration (as an indicator of pesticide exposure in the body) and iodine status of women in the endemic goiter area.Methods: The study was conducted in Pakis sub district, Magelang Regency, Central Java on July to November 2005. The design of the research was "cross-sectional" study. Samples were 265 women of child bearing age (17-35 years old). The data collected were concentration of free T4 (FT4) , cholinesterase enzyme in plasma, intake of cyanide originated from food, concentration of urine iodine excretion (UIE), type of contraception used and nutritional status. The concentration of serum FT4 were divided into two group (< 0.79 ng/gL = low > nonnal). These data were analyzed by using chi-square test with odd ratio at 95% CL. Association between independent and dependent variables by controlling other variable were analyzed by multiple logistic regression.Results: Pesticides that frequently used in the area of study was Organophosphate and Carbamat The pesticide residue on raw vegetables was Carbofuran. Its concentration was 0.056 to 55.65 mg/kg. The highest residues was found in cabbage and it had exceeded the maximum limit of permitted residue. The pesticide residue of cooked vegetables was very low. Low concentration of cholinesterase enzyme (< 3600 U/L) was found in 3.8% women. More than 29% had low iodine status. Logistic regression analysis showed that women exposed to pesticide had 33 fold greater risk for IDD than that of without any pesticide exposure.Conclusions: The highest concentration of pesticide residue was obtained on raw cabbage and raw mustard green. It ranged from 2 to 10 times of maximum limit permitted residue according to Ministry of Health. Percentage of women who exposed by pesticide (carbamat) was 3.8%. It was showed that 29.3% of woman has low iodine status. Women exposed to pesticide had 100 risk 33 fold greater than that without any cyanide exposure.Suggestions: To minimize the hazardous effect of pesticide on health, it is suggested that the vegetables should be cooked property before consuming. It is necessary to do further research by takilg account the effect of cyanide air pollution inhaled besides cyanide from food. The more intensive control of using pesticide needs to be doneperiodically.Keywords: cholinesterase enzyme, iodine status and endemic goiter